The Impact of Rate Changes: A Comparative Study on Food and Beverage Companies - Ersa Meilinda; Rosiliyah; Ario Purdianto (Indonesian Journal of Business Analytics, 2025)
The purpose of this study was to determine the differences in sales, operating costs, and net income before and after the 11% income tax rate increase. The population in this study were non-cylical consumer companies with a research sample of 24 food and beverage sub-sector companies eliminated by several criteria. The research method used is descriptive and comparative statistics with normality tests, assumption tests, and different tests, researchers use the help of SPSS software version 22. The results showed that there were differences in sales because the increase in VAT had an impact on the increase in selling prices. Then, there are differences in operating costs because VAT is attached to the price of raw materials that the company will purchase, resulting in an increase in the cost of goods manufactured. The increase in the cost of goods produced has an impact on increasing operating costs. Meanwhile, there is no difference in net profit before and after the VAT increase, this is because the company's profit is not directly related to changes in VAT because it has been considered at the time of charging operational costs and the company's profit is more dominantly influenced by changes in income tax.